Upper Ordovician chronostratigraphic correlation between the Appalachian and Midcontinent basins - Cristiana J. P. Esteves; Patrick I. McLaughlin; Alyssa M. Bancroft; Thomas W. Wong Hearing; Mark Williams; Jahandar Ramezani; Poul Emsbo; Thijs R. A. Vandenbroucke (Estonian Journal of Earth Sciences, 2023)
Study of a subsurface core (named F688) from northern Indiana provides integrated data sets linking Katian chronostratigraphic records of the Appalachian and Midcontinent basins. The F688 core shows a variety of shallow- and deep-water facies containing numerous, well-preserved and zonally significant fossil species and diagnostic chemostratigraphic patterns. The succession belonging to the Cincinnatian Regional Stage in the F688 core is 210 m thick. Detailed benchtop examination of the succession revealed several phosphatic intervals, rich brachiopod faunas, multiple graptolitic horizons, and at least two tephras. Elemental analysis was conducted at 60 cm spacing quantifying lithofacies composition. Based on these results, the succession was assigned to six previously defined lithostratigraphic units (Kope, Waynesville, Liberty, Whitewater, Elkhorn, and Fort Atkinson formations). This lithostratigraphic succession shares components with both the Appalachian and Midcontinent basins, suggesting deposition near their shared margin. Twenty samples yielded abundant, well-preserved, low-diversity conodont assemblages with long-ranging taxa that clearly demarcate the position of the OrdovicianâSilurian boundary at the top of the succession in the core. More than fifty palynologic samples, targeting graptolite-bearing intervals, were processed for chitinozoans and produced important new insights. The Kope Formation contains the chitinozoan species Belonechitina kjellstromi, Hercochitina downiei, and Clathrochitina sp. nov., co-occurring with a graptolite assemblage suggestive of the Geniculograptus pygmaeus Zone. Samples from the overlying Waynesville Formation produced graptolites indicative of the upper G. pygmaeus to Paraorthograptus manitoulinensis zones co-occurring with the long-ranging chitinozoan species Belonechitina micracantha and Plectochitina spongiosa as well as several new species of the genera Tanuchitina and Hercochitina. Higher in the core, the Liberty, Whitewater, Elkhorn, and Fort Atkinson formations yielded chitinozoan species characteristic of the upper Katian biozones of Anticosti Island and Nevada, such as Tanuchitina anticostiensis, Hercochitina longi, and Eisenackitina ripae. Results of Î´13Ccarb analysis reveal partial preservation of the Kope, Waynesville, and Elkhorn excursions. A tephra in the rising limb of the Waynesville Excursion yielded needle-shaped clear zircons that will provide a high-precision U-Pb age. The Fort Atkinson Formation is overlain by the Brassfield Formation containing Silurian conodonts and Î´13Ccarb values suggesting an Aeronian age.